A study on the information-seeking behavior of students in selected high schools in Novaliches, Quezon City regarding adolescent sexuality - Adolfo, Jill Anne L. (2011)
Adolescence is a crucial stage in one's life wherein many life-changing events occur. It is also the stage where naturally occurring phenomenon such as sexual impulses and socializing agents such as one's environment influence the decision making and actions of the individual. This study attempted to describe the information-seeking behavior of selected third year and fourth year high school students in public and private schools in Novaliches, Quezon City.